Characteristics of Aerosol Size Distributions and New Particle Formation Events at Delhi: An Urban Location in the Indo-Gangetic Plains - Jose, Sandhya; Mishra, Amit Kumar; Lodhi, Neelesh K.; Sharma, Sudhir Kumar; Singh, Sachchidanand (Frontiers in Earth Science, 2021)
Accurate information about aerosol particle size distribution and its variation under different meteorological conditions are essential for reducing uncertainties related to aerosol-cloud-climate interaction processes. New particle formation (NPF) and the coagulation significantly affect the aerosol size distribution. Here we study the monthly and seasonal variability of aerosol particle size distribution at Delhi from December 2011 to January 2013. Analysis of aerosol particle size distribution using WRAS-GRIMM reveals that aerosol particle number concentration is highest during the post monsoon season owing to the effect of transported crop residue and biomass burning aerosols. Diurnal variations in number concentration show a bimodal pattern with two Aitken mode peaks in all the seasons. Monthly volume size distribution also shows bi-modal distribution with distinct coarse and fine modes. NPF events are observed less frequently in Delhi. Out of 222 days of WRAS data, only 17 NPF events have been observed, with higher NPF frequency during summer season. Growth rate of the nucleation mode of NPF events vary in the range 1.88–21.66 nm/h with a mean value of ∼8.45 ± 5.73 nm/h. It is found that during NPF events the Aitken and nucleation mode particles contribute more to the number concentration. Simultaneous measurement of UV flux and particulate matter (PM10 and PM2.5) have also been done along with particle number size distribution measurement to understand the possible mechanisms for NPF events over the study location.